Enlarged perivascular spaces in the basal ganglia region are associated with white matter interstitial fluid content via deep medullary vein dysfunction - Lan, Haiyuan; Lei, Xinjun; Wang, Qingchun; Wang, Lebing; Li, Kunwang (Frontiers in Human Neuroscience, 2025)
ObjectiveTo investigate the effect of enlarged perivascular spaces in the basal ganglia (BG-EPVS) on interstitial fluid (ISF) content in white matter and to assess the mediating role of deep medullary vein (DMV) dysfunction in this relationship among patients with cerebral small vessel disease (CSVD).MethodsMagnetic resonance imaging and clinical data were collected from 166 patients with CSVD. EPVS score (0–4) was evaluated on T2-weighted images on the basis of the number of EPVS in a single slice. DMV score (0–18) was assigned on susceptibility-weighted imaging according to signal continuity and clarity. Free water (FW) values, representing ISF content in white matter, were derived from diffusion tensor imaging.ResultsThe mean age of the participants was 63.6 ± 11.1 years. The median score was as follows: BG-EPVS, 1 (IQR: 1–2); centrum semiovale EPVS (CSO-EPVS), 1 (IQR: 1–2); CSVD score, 1 (IQR: 0–2), and DMV, 4 (IQR: 1–11). The mean FW values were 0.25 ± 0.02. No significant correlation was observed between CSO-EPVS and FW (r = 0.112, p = 0.119). In contrast, BG-EPVS showed a moderate positive correlation with both DMV score (r = 0.594, p < 0.001) and FW (r = 0.521, p < 0.001). DMV score was also moderate positively correlated with FW (r = 0.557, p < 0.001). These associations remained significant after adjusting for age, sex, and vascular risk factors (all p < 0.05). Mediation analysis confirmed that DMV score significantly mediated the relationship between BG-EPVS and FW, independent of covariates.ConclusionHigher BG-EPVS score is significantly associated with increased ISF content in white matter, with DMV dysfunction serving as a key mediator of this association.